The Effects of Different Storage Conditions and Repeated Freeze/Thaw Cycles on the Concentration, Purity and Integrity of Genomic DNA - Šafaříková, Markéta; Kuběna, Aleš; Franková, Věra; Zíma, Tomáš; Kalousová, Marta (Folia biologica (Praha), 2021)
The crucial requirement of molecular genetic methods is high-quality input material. The key question is "how to preserve DNA during long-term storage." Biobanks are recommended to aliquot isolated DNA into provided volumes. The aim of this study was to analyse the effect of repeated freezing and thawing on the genomic DNA integrity, quality and concentration. The aliquoted DNA isolated from blood cells using the automatic MagNA system and manual salting out method underwent freeze/thaw cycles at different storage conditions (-20 °C, -80 °C and liquid nitrogen). The average initial concentrations were 270.6 ng/μl (salting out method) and 125.0 ng/μl (MagNA). All concentration deviations relative to the concentration after the first freeze/ thaw cycle were less than 5 % for -20 °C and -80 °C cycling with both isolation methods. The average percentage differences of liquid nitrogen samples were higher, and the MagNA isolation method showed significant differences. There were no significant changes in the DNA purity or quality. The repeating freeze/ thaw up to 100 cycles (through -20 °C and -80 °C, respectively) did not significantly influence the integrity, concentration, or purity of genomic DNA, suggesting that storage of samples in high-volume pools without multiple aliquoting is possible. Storage in a freezer seems to be the most suitable way of long-term DNA preservation, because liquid nitrogen storage leads to formation of DNA clumps.
Keywords: Genomics; DNA; Freezing; zmrazování; genomika